IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN BANKING SECTOR DURING THE COVID-19 PANDEMIC - Xiaoxia, Hu; Sukran, Sukran; Nurhalizah, Hayyumu Farina (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2023)
In order to successfully implement Corporate Social Responsibility (CSR) in the banking industry, it is crucial to understand the factors that influence it and the impacts caused. This research is useful for future researchers who examine Corporate Social Responsibility and functions as decision-making materials for banking sector practitioners. This study employs a systematic literature review method of 32 articles relevant to the research questions. This study found that there are 11 factors influencing Corporate Social Responsibility and 22 impacts of it. However, this research is still limited to one source database. Therefore, it is advised that future scholars include other databases to improve the study.